Sentimental Sustainability: Does What Companies Say Tell More Than What Companies Do? - Konstantin Ignatov; Markus Rudolf (Financial Markets, Institutions & Instruments, 2023)
Based on a sample of more than eleven thousand unique 10-K reports of US companies filed with SEC in period 2013 to 2018, this study examines the relationship between actual sustainability performance of companies, evaluated by MSCI ESG performance scores, and the extent and the scope of environmental, social, and governance information disclosure in their annual reports. The study shows empirical evidence supporting the signalling theory view of voluntary disclosure of ESG information in annual reports for most industries, while environmentally unfriendly companies belonging to the Mining industry division show excessive reporting behavior favoring environmental topics, which is consistent with incentives to improve public image and mitigate social, political, and legal risks in line with the legitimacy theory of information disclosure. When differentiating between forward-looking and non-forward-looking ESG statements, the study shows that companies providing more forward-looking ESG information in annual reports show better next-year ESG performance. This study implements established content analysis techniques with focus on ESG reporting and performance, building up on the study of Baier, Berninger, and Kiesel (2020) that proposed an ESG-tailored dictionary for textual analysis purposes.
Keywords: 330